PENGARUH LITERASI EKONOMI DAN SELF CONTROL TERHADAP PERILAKU KONSUMTIF MAHASISWA PRODI PENDIDIKAN EKONOMI - Bobi, Yopinus (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The rise in public consumption is one of the effects of globalization, but an economy dependent on it will deteriorate if left unchecked for an extended period of time. The purpose of this study is to determine how Economic literacy and self-control affect consumer behavior among STKIP Persada Khatulistiwa economic education study program participants. Correlational study employing quantitative techniques is the methodology used. In this study, 73 respondents from the classes of 2020, 2021, and 2022 made up the sample. A questionnaire was utilized to obtain the data. The SPSS version 25 application is used for data analysis along with the t test, f test, normality test, heteroscedasticity test, multicollinearity test, multiple regression analysis, and analysis of the coefficient of determination. The study's findings indicate that self-control and Economic literacy both have an impact on consumer behavior, with a combined effect on consumption behavior of 46.5%, with the remaining 53.5% being explained by other factors. Self-control also has an impact on consumer behavior patterns